2013
DOI: 10.1371/journal.pone.0078656
|View full text |Cite
|
Sign up to set email alerts
|

Gefitinib Inhibits Invasive Phenotype and Epithelial-Mesenchymal Transition in Drug-Resistant NSCLC Cells with MET Amplification

Abstract: Despite the initial response, all patients with epidermal growth factor receptor (EGFR)-mutant non-small cell lung cancer (NSCLC) eventually develop acquired resistance to EGFR tyrosine kinase inhibitors (TKIs). The EGFR-T790M secondary mutation is responsible for half of acquired resistance cases, while MET amplification has been associated with acquired resistance in about 5-15% of NSCLCs. Clinical findings indicate the retained addiction of resistant tumors on EGFR signaling. Therefore, we evaluated the mol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
29
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 49 publications
3
29
0
Order By: Relevance
“…This could be caused by increased expression of TGF-β (52). Surprisingly, drug-withdrawal may further enhance the EMT state due to an EGFR-mediated boost of a partial EMT existing in a "ready-to-go" fashion (63). A recent study suggested a role for TGF-β in mediating the RTK switch with accompanying activation of AKT and EMT, hence, rendering cells independent of EGFR signaling (52).…”
Section: Receptor Tyrosine Kinases (Rtks)mentioning
confidence: 99%
“…This could be caused by increased expression of TGF-β (52). Surprisingly, drug-withdrawal may further enhance the EMT state due to an EGFR-mediated boost of a partial EMT existing in a "ready-to-go" fashion (63). A recent study suggested a role for TGF-β in mediating the RTK switch with accompanying activation of AKT and EMT, hence, rendering cells independent of EGFR signaling (52).…”
Section: Receptor Tyrosine Kinases (Rtks)mentioning
confidence: 99%
“…S3A). Next, a Cre-inducible allele of the MET receptor tyrosine kinase, which is associated with EMT and therapy resistance (18,19), and expressed at high levels in breast cancer (20)(21)(22), was introduced in KB1P-Col1a1 ESC clone A2.1 to produce K14cre;Brca1 F/F ; Trp53 F/F ;Col1a1 inv-CAG-Met-Luc (KB1P-MET) ESCs (Fig. S3B).…”
Section: Met Accelerates Mammary Tumor Development In Kb1p Chimericmentioning
confidence: 99%
“…Clinical studies demonstrated that certain EGF receptor-mutated patients could benefit from a second-line therapy including gefitinib and erlotinib through reversal of drug resistance. The data showed that gefitinib and erlotinib could reduce cell migration and invasion and prevent EMT from developing [59]. These phenomena offer an interesting treatment approach if these substances are well tolerated and able to be combined with conventional or targeted therapies where there is evidence of EMT-mediated resistance.…”
Section: Therapeutic Strategy For Drug Resistance Via Emtmentioning
confidence: 99%